2020
DOI: 10.3390/catal10020190
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Biodiesel Synthesis from Honne-Rubber-Neem Oil Blend with a Novel Mesoporous Base Catalyst Synthesized from a Mixture of Three Agrowastes

Abstract: Application of solid catalysts synthesized from agricultural wastes provides an environmentally benign and low-cost process path to synthesize biodiesel. An ash containing an equal mixture of cocoa pod husk, plantain peel and kola nut pod husk ashes (CPK) was obtained by open combustion of each of the biomass in air and calcined at 500 °C for 4 h. The calcined CPK ash was characterized to determine its catalytic potential. Two-level transesterification technique was used to synthesize biodiesel using the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 56 publications
3
56
1
Order By: Relevance
“…Table 6 3.6 Comparative studies of this work with earlier reported works Table 7 showed the use of single heterogeneous based catalyst derived from different agricultural wastes for biodiesel production using single/blended oil in a different ratio [8,27,28]. Falowo et al [17] derived respect on earlier reports, there exists no basis, but this study showed that the derived catalysts produced a high yield of biodiesel, and the catalysts can be used in industrial as feedstock.…”
Section: Sem Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…Table 6 3.6 Comparative studies of this work with earlier reported works Table 7 showed the use of single heterogeneous based catalyst derived from different agricultural wastes for biodiesel production using single/blended oil in a different ratio [8,27,28]. Falowo et al [17] derived respect on earlier reports, there exists no basis, but this study showed that the derived catalysts produced a high yield of biodiesel, and the catalysts can be used in industrial as feedstock.…”
Section: Sem Analysismentioning
confidence: 92%
“…Further study by Hadiyanto et al [15] utilized Anadara granosa as a heterogeneous CaO-based catalyst, but, Trisupakitti et al [16] used golden apple cherry snail as a heterogeneous catalyst to synthesized biodiesel from the vegetable. Falowo et al [17] developed a new base catalyst from a combination of biomass wastes. All these reports developed catalysts from mixture or single solid wastes, and applied it to the synthesis of biodiesel from vegetable oil or its blend, except in the work of Adepoju, (2020) [18] where two derived base catalysts were tested on the synthesized biodiesel from the blended oil.…”
Section: Introductionmentioning
confidence: 99%
“…Table 7 showed the use of single heterogeneous based catalyst derived from different agricultural wastes for biodiesel production using single/blended oil in a different ratio [8,27,28]. Falowo et al [17] derived a based catalyst from the mixture of three agricultural wastes, while Adepoju et al in their various reported studies, derived novel based catalysts from the mixture of different biomass wastes for biodiesel synthesis.…”
Section: Fatty Acid Ethyl Ester (Faees) Qualities and Its Comparison mentioning
confidence: 99%
“…Further study by Hadiyanto et al (2016) [15] utilized Anadara granosa as a heterogeneous CaO-based catalyst, but, Trisupakitti et al (2019) [16] used golden apple cherry snail as a heterogeneous catalyst to synthesized biodiesel from the vegetable. Falowo et al (2020) [17] developed a new base catalyst from a combination of biomass wastes. All these reports developed catalysts from mixture or single solid wastes, and applied it to the synthesis of biodiesel from vegetable oil or its blend, except in the work of Adepoju, (2020) [18] where two derived base catalysts were tested on the synthesized biodiesel from the blended oil.…”
Section: Introductionmentioning
confidence: 99%